Serological Survey of Canine Vector-Borne Infections in North-Center Spain - Pérez Pérez, Patricia; Rodríguez-Escolar, Iván; Carretón, Elena; Sánchez Agudo, José Ángel; Lorenzo-Morales, Jacob; Montoya-Alonso, José Alberto; Morchón, Rodrigo (Frontiers in Veterinary Science, 2021)
Various factors are currently causing an increase in vector-borne parasitic diseases at global scale, among them some stand out, such as climatic disturbances derived from global change, the increase in movements of reservoir animals, or changes in land made by human activity. In the European continent there has been an increasing number of epidemiological studies focused on the detection of this diseases, especially in dogs. In Spain there are few epidemiological studies focused on the evaluation of the biotic and abiotic factors that may influence the distribution, such as climatic zones, orography or presence of water reservoirs. The aim of this study was to analyze the prevalence and distribution of several canine vector-borne diseases caused by Dirofilaria immitis, Leishmania infantum, Anaplasma platys and Erhlichia canis in the autonomous community of Castilla y León, the largest region of the Iberian Peninsula, providing a geospatial approach based on a Geographic Information Systems (GIS) analysis. Blood from a total of 1475 domestic dogs from the 9 provinces of Castilla y León were analyzed. Also, a GIS analysis of the sample locations was carried out, taking into account the most important predictor variables. The prevalence in dogs infected by D. immitis was 7.19%, and the seroprevalence by L. infantum was 4.61% and 1.56% for A. platys and E. canis. Most of the infected animals were located in areas with stagnant water, irrigated agriculture or riverbanks, always close to forest and woodland vegetation. These results indicate that dogs living in Castilla y León should take prophylactic measures to avoid infections.